Planejamento de redes de comunicação sem fio para ambiente indoor considerando os efeitos da polarização das antenas: abordagem baseada em medições - RODRIGUES, Josiane do Couto (Universidade Federal do Pará, 2012)
A major application of electromagnetic waves, presently, in the area of telecommunications concern to links of wireless mobile systems. Be these terrestrial ones (indoor/outdoor) or via satellite, the designer of the telecommunications system must be able to determine the irradiate systems, the powers involved, the operation frequency of the system, the coverage area and the quality of service parameters. The planning of new wireless communications networks represents a great challenge to include advanced services with different quality requirements, the mobility support, high transmission rates and high traffic capacity. The several environments in which those networks operate and the associated phenomena produce several effects on the behavior of the received sign and, consequently, a variation in the performance of the communication link among the points of access to net and the users. Consequently, those effects should be appraised correctly, in such a way that the network dimensioning assists to the quality requirements regulated. The present work aims to establish a methodology for the planning of wireless networks for environments indoor, considering the parameters of the quality of services and the effects of the polarization of the antennas. An empiric model is proposed to determine the coverage area of that environment from an approach based in measurements. As a result of measurement campaigns, they were identified the main parameters that interfere in the losses in the propagation link. Standing out the materials involved in the environment as well as the polarization effects of the transmitter’s antennas, among others. Such effects, if evaluated correctly, they will allow to the planner’s net, in a critical way and with base in data obtained in field, to define the best parameters of configuration and project criteria for the implantation of a wireless mobile network. The measurements for determination of the covering parameters and of quality of services they were accomplished at the building of the Laboratório de Engenharia Elétrica e de Computação and in the classes building of the Instituto de Tecnologia da Universidade Federal do Pará. The measurement campaigns were used some frequencies, chosen due to the importance of the services available: 2,4 GHz - local nets without thread (WLAN's); 3,5 GHz - licensed WiMAX; 5,85 GHz - free WiMAX and 10 GHz (9,8 to 10 GHz band is not yet regulated, 10 - 10,15 GHz Amateur radio band (Anatel resolution, No. 452/2006 - D.O.U. from 20.12.2006) or multimedia communications services (SCM) for broadband systems). The main results obtained with the proposed model were evaluated and compared with the main models of the literature and showed that the methodology adopted for the networks planning of wireless communications in indoor environment had a good performance.